Matrix Gla protein gene expression and protein accumulation co-localize with cartilage distribution during development of the teleost fish Sparus aurata - Pinto, Jorge (2014)
Matrix Gla protein (MGP) is a member of the family of extracellular mineral-binding Gla proteins, expressed in several tissues with high accumulation in bone and cartilage. Although the precise molecular mechanism of action of this protein remains unknown, all available evidence indicates that MGP plays a role as an inhibitor of mineralization. We investigated the sites of gene expression and protein accumulation of MGP throughout development of the bony fish Sparus aurata, by in situ hybridization, Northern and RT-PCR Southern hybridization, and immunohistochemistry. The results obtained were compared with the patterns of developmental appearance of cartilaginous and mineralized structures in this species, identified by histological techniques and by detection of mRNA presence and protein accumulation of osteocalcin (Bone Gla protein), a marker for osteoblasts known to accumulate in bone mineralized extracellular matrix.